2021
DOI: 10.1080/23311908.2021.1875549
|View full text |Cite
|
Sign up to set email alerts
|

Visual Communication Analysis (VCA): Implementing self-determination theory and research-based practices in special education classrooms

Abstract: The number of students with disabilities served under the federal law of the Individuals with Disabilities Education Act (IDEA) in public schools increased from 6.4 million to 7.0 million students from 2011 to 2017. Current curriculum offered to special needs students is eclectic and inconsistent as they vary across students, classrooms, districts, and throughout the nation. The current study examined the use of Visual Communication Analysis (VCA) within moderate to severe special education classes. Researcher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…The rate of acquisition and learning is much faster. Other research has found this to be true for older children however, replication of this study can determine if this is also true for very young children as was found in this case study [15,16].…”
Section: Areas For Future Studysupporting
confidence: 72%
See 1 more Smart Citation
“…The rate of acquisition and learning is much faster. Other research has found this to be true for older children however, replication of this study can determine if this is also true for very young children as was found in this case study [15,16].…”
Section: Areas For Future Studysupporting
confidence: 72%
“…VCA combines SDT principles in combination with visual supports, prompts, and technology-aided instruction. Research on VCA has illustrated significant decreases in maladaptive and self-injurious behaviors, as well as the ability to communicate via typing independently [15,16]. The purpose of this study was to assess any benefits of VCA when applied as an early intervention and as an assessment method.…”
Section: Executive Functionmentioning
confidence: 99%
“…Creating spaces that support these three psychological needs can foster children's creativity, motivation, and school engagement (18). Children with SLCD could particularly benefit from interventions that support their autonomy, competence, and relatedness, as they face additional challenges in these domains (19). Indeed, autonomy, supportive experiences, feeling connected to peers, and tasks that enable a sense of competence can all contribute to emotion expression through introspection and self-understanding (20).…”
Section: Slcd and Self-determination Theorymentioning
confidence: 99%
“…On its generalization to untrained talents (i.e., social abilities), as well as their long-term impacts, there is a lack of research. Shkedy et al (2021) stated from 2011 to 2017; there were 7.0 million children with disabilities enrolled in public schools that were covered by the Participants with Disorders Education Act (IDEA), a federal legislation. The current curricula provided to students with special needs are diverse and incoherent because they differ amongst students, classes, districts, and the entire country.…”
Section: Literature Reviewmentioning
confidence: 99%